Broadway musicals : the 101 greatest shows of all time - Bloom, Ken, 1949-; Vlastnik, Frank (New York : Distributed by Workman Pub. Co., 2004)
Chronicles over on hundred years of the most popular Broadway musicals and their performers, directors, composers, writers, and designers and includes eight hundred fifty black-and-white and full-color illustrated photographs, plot synopses, cast and song lists, and production details.
Includes index.
Reference and Research Book News.
Adult
Keywords: Musicals -- New York (N.Y.) -- Encyclopedias; Musicals -- New York (N.Y.) -- Encyclopedias